Bioactive and yield potential of jelly palms (Butia odorata Barb. Rodr.). (1st April 2015) - Beskow, Günter Timm; Hoffmann, Jessica Fernanda; Teixeira, Andrea Miranda; Fachinello, José Carlos; Chaves, Fábio Clasen; Rombaldi, Cesar Valmor
Highlights: Bioactive and yield potential of five genotypes of jelly palm Butia odorata . The highest yielding genotype was low in bioactive content. The red genotype had highest anthocyanin content and highest antioxidant potential. Abstract: In this descriptive study, Butia odorata genotypes were evaluated for yield, fruit number, pulp yield, bioactive content (including phenolic compounds, carotenoid, anthocyanin, l -ascorbic acid, and fibre content), antioxidant potential, and phenotypic characteristics. Genotype 117 was the highest yielding, with an estimated fruit yield of 22, 000 kg ha −1 and pulp yield of 12, 000 kg ha −1 . On the other hand, the lowest yielding genotype, accession 49, showed an estimated fruit yield of 8400 kg ha −1 . Jelly palm fruit were generally rich in phenolic content (280.50–398.50 mg 100 −1  g), carotenoid content (2.80–4.08 mg 100 g −1 ), andl -ascorbic acid content (34.63–63.84 mg 100 g −1 ). While the highest yielding genotype was not the richest in bioactive content, the lowest yielding genotype showed the highestl -ascorbic acid content. Although fruit yield and phytochemical composition are desirable attributes in jelly palm fruit, none of the genotypes evaluated showed high levels of both. Therefore, fruit yield and bioactive phytochemical content appear to be inversely proportional.